Manual de procedimientos para la mejora de las funciones de innovación tecnológica en el Hotel Perla Spondylus en Manta - Cueva Solórzano, Angy Katherine (2021)
The objective of the work was to develop a procedures manual that contributes to the improvement of the technological innovation (IT) functions at the Hotel Perla Spondylus in Manta. The research was descriptive and explanatory with a mixed approach (qualitative-quantitative). The development of the research was carried out in three phases, the first phase was aimed at diagnosing the current situation of the hotel where the characterization of the services offered is carried out. Subsequently, an analysis of the company was carried out, strengthening with a strategic SWOT, where it was known that the hotel is privileged due to its strategic location, taking into account the opportunity to link with travel agencies, improving the marketing and innovation processes and this way tourism competitiveness is increased. The second phase aimed at evaluating IT functions, in which the hotel functions were determined, obtaining that it is important to improve technology aspects, so that the identified processes, which are 5, help the proper functioning of the establishment. In the third phase, the procedures manual was designed, which consists of an introduction, objectives, justification, scope, identification of the processes, this manual contributes to a better organization around the identified processes. As a conclusion, a proposal was made based on technological indicators in order to guarantee the viability of the manual through the control and monitoring of the manual as a support document for the hotel in the performance of its activities and technological processes.